The tigers of the Kumgang mountains a Korean folktale - Kim, So-un 1907-; Chæong, Kyæong-sim 1975- (Rutland, Vt. Tuttle Publishing, 2005)
A young man practices for years to become a great marksman, and goes into the Kumgang mountains of Korea to hunt the tigers that killed his father.
Keywords: Hunters -- Korea -- Folklore; Tiger -- Korea -- Folklore; Hunters -- Folklore; Tiger -- Folklore; Korea -- Folklore